2014
DOI: 10.1007/s11999-013-3047-y
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Tibial Coverage Is Detrimental to Proper Rotational Alignment

Abstract: Background Traditionally, the placement of the tibial component in total knee arthroplasty (TKA) has focused on maximizing coverage of the tibial surface. However, the degree to which maximal coverage affects correct rotational placement of symmetric and asymmetric tibial components has not been well defined and might represent an implant design issue worthy of further inquiry. Questions/purposes Using four commercially available tibial components (two symmetric, two asymmetric), we sought to determine (1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 20 publications
5
70
0
Order By: Relevance
“…Our results with regard to tibial surface coverage are consistent with those found by Wernecke et al and Martin et al, who performed studies with a similar methodology for symmetric and asymmetric trays [9,11]. Dai et al investigated anatomic, symmetric, and asymmetric trays in multiple ethnicities for healthy knees [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results with regard to tibial surface coverage are consistent with those found by Wernecke et al and Martin et al, who performed studies with a similar methodology for symmetric and asymmetric trays [9,11]. Dai et al investigated anatomic, symmetric, and asymmetric trays in multiple ethnicities for healthy knees [10].…”
Section: Discussionsupporting
confidence: 91%
“…Proper tibial rotation avoids excess risk of MCL tension [2], contact stress [3], knee pain [4,5], stiffness [6], and patellofemoral complications [7,8]. Different tibial tray designs offer varying potential in optimizing the relationship between tibial surface coverage and rotation [9]. An anatomic tibial tray was recently developed in an effort to better match patient anatomy compared to symmetric and asymmetric trays.…”
mentioning
confidence: 99%
“…Some surgeons use an asymmetric component and maximize tibial coverage to obtain the best stability and load transfer [45,46]. Additionally, Martin et al [47] recently reported that it is easier to balance rotation and coverage with asymmetric tibial base plates than symmetrical tibial designs, which were evaluated in the current study. The strengths of this study include that all patients were treated by a single experienced surgeon, and that comparisons were conducted between PCL-retaining and PCL-substituting mobile-bearing designs.…”
Section: Discussionmentioning
confidence: 89%
“…Most studies 13,14 which demonstrate the superiority of asymmetric tibial base plates over symmetric tibial base plates have not been done on cases of post knee replacement patients, but they have been done on hypothetical computer generated models of anthropometric western tibia; ignoring the fact that the tibial base plate has to be implanted matching the external rotation of the femoral component. External rotation of the femoral component differs from patient to patient and population to population.…”
Section: Flexion Contracture In Degreesmentioning
confidence: 99%
“…12,13 Traditionally, it has been proposed that maximizing tibial coverage to increase fixation by improving load transfer from the implant to the proximal tibia avoids subsidence and loosening. 14 Asymmetric tibial trays are claimed to be more anatomic in nature and therefore cover the tibial plateau more completely than symmetric tibial trays 15 ; thus decreasing the incidence of tibial tray overhang and subsidence. However, tibial coverage rarely exceeds 78% and several authors have proposed a minimum of 75% coverage for adequate fixation.…”
Section: Introductionmentioning
confidence: 99%